Disease Control Priorities Third Edition: Time to Put a Theory of Change Into Practice; Comment on "Disease Control Priorities Third Edition Is Published: A Theory of Change Is Needed for Translating Evidence to Health Policy" - Wanrudee Isaranuwatchai; Ryan Li; Amanda Glassman; Yot Teerawattananon; Anthony J. Culyer; Kalipso Chalkidou (Kerman University of Medical Sciences, 2019)
The Disease Control Priorities program (DCP) has pioneered the use of economic evidence in health. The theory of change (ToC) put forward by Norheim is a further welcome and necessary step towards translating DCP evidence into better priority setting in low- and middle-income countries (LMICs). We also agree that institutionalising evidence for informed priority-setting processes is crucial. Unfortunately, there have been missed opportunities for the DCP program to challenge ill-judged global norms about opportunity costs and too little respect has been shown for the wider set of local circumstances that may enable, or disable, the productive application of the DCP evidence base. We suggest that the best way forward for the global health community is a new platform that integrates the many existing development initiatives and that is driven by countries' asks.